DESIGN OF PJBL LEARNING MODEL IN ELECTRICAL ENERGY CONVERSION COURSE - ANDI SYARIFUDDIN; HAMSU ABDUL GANI; MUHAMMAD YUSUF MAPPEASSE (Jurnal Vokasi Keteknikan, 2024)
The rapid advancement of technology and the complexity of electrical energy systems necessitate innovative educational approaches in electrical engineering. This study presents a Project-Based Learning (PJBL) model tailored for the Electrical Energy Conversion course, designed to enhance students' understanding and practical skills through real-world projects mirroring industry practices. The model's key components include interdisciplinary projects, collaborative learning environments, and iterative feedback mechanisms. The initial implementation with electrical engineering students involved surveys, interviews, and performance assessments, demonstrating significant improvements in student engagement, comprehension of course material, and overall academic performance. The findings suggest that the PJBL model is an effective pedagogical strategy for teaching complex subjects like electrical energy conversion. Further research is recommended to refine the model and explore its applicability across different courses and educational contexts.